The Woman as Wolf (AT 409): Some Interpretations of a Very Estonian Folk Tale - Metsvahi, Merili (Estonian Literary Museum, the Estonian National Museum and the University of Tartu, 2023)
The article analyses tale type The Woman as Wolf, which is one of the most popular folk tales in the Estonian Folklore Archives and is represented there both in the form of a fairy tale and in the form of a legend. The vast majority of the versions of The Woman as Wolf were written down in the first part of the 20th century within Estonia and where recorded from Estonians. The article introduces the content of the tale, the origin of the first records from the early 19th century, and the dissemination area of the tale, which remains outside Western Europe: apart from the Estonian versions there are Sami, Karelian, Vepsian, Livonian, Latvian, Lithuanian, Russian, Ukrainian and Belarusian versions. While in almost all the Estonian versions the main protagonist is transformed into a wolf, in most of the versions written down in other areas and ethnic groups, another animal or bird replaces the wolf. The author is of the opinion that the Finnic area is central to the distribution of the folk tale The Woman as Wolf. The animal the woman is transformed into in the plot would not have been a wolf in earlier times. The article provides an explanation why the wolf is predominant in Estonian written sources. For that purpose the ways in which the wolf and werewolf were perceived in earlier Estonian folk belief are introduced. At the end of the article interpretation of the folk tale is provided. The author states that the plot and some of the motifs found in this folk tale reflect the difficulties women had in submitting to the norms and values of patriarchal order within their society.